Gene expression and physiological changes of different populations of the long-lived bivalve Arctica islandica under low oxygen conditions. - Eva E R Philipp; Wiebke Wessels; Heike Gruber; Julia Strahl; Anika E Wagner; Insa M A Ernst; Gerald Rimbach; Lars Kraemer; Stefan Schreiber; Doris Abele; Philip Rosenstiel (PLoS ONE, 2012)
The bivalve Arctica islandica is extremely long lived (>400 years) and can tolerate long periods of hypoxia and anoxia. European populations differ in maximum life spans (MLSP) from 40 years in the Baltic to >400 years around Iceland. Characteristic behavior of A. islandica involves phases of metabolic rate depression (MRD) during which the animals burry into the sediment for several days. During these phases the shell water oxygen concentrations reaches hypoxic to anoxic levels, which possibly support the long life span of some populations. We investigated gene regulation in A. islandica from a long-lived (MLSP 150 years) German Bight population and the short-lived Baltic Sea population, experimentally exposed to different oxygen levels. A new A. islandica transcriptome enabled the identification of genes important during hypoxia/anoxia events and, more generally, gene mining for putative stress response and (anti-) aging genes. Expression changes of a) antioxidant defense: Catalase, Glutathione peroxidase, manganese and copper-zinc Superoxide dismutase; b) oxygen sensing and general stress response: Hypoxia inducible factor alpha, Prolyl hydroxylase and Heat-shock protein 70; and c) anaerobic capacity: Malate dehydrogenase and Octopine dehydrogenase, related transcripts were investigated. Exposed to low oxygen, German Bight individuals suppressed transcription of all investigated genes, whereas Baltic Sea bivalves enhanced gene transcription under anoxic incubation (0 kPa) and, further, decreased these transcription levels again during 6 h of re-oxygenation. Hypoxic and anoxic exposure and subsequent re-oxygenation in Baltic Sea animals did not lead to increased protein oxidation or induction of apoptosis, emphasizing considerable hypoxia/re-oxygenation tolerance in this species. The data suggest that the energy saving effect of MRD may not be an attribute of Baltic Sea A. islandica chronically exposed to high environmental variability (oxygenation, temperature, salinity). Contrary, higher physiological flexibility and stress hardening may predispose these animals to perform a pronounced stress response at the expense of life span.